The legal position and constitutional framework in the implementation of Islamic criminal law - Shuaib, Farid Sufian (2017)
Similar to Aceh, Malaysia has a plural court system and the Syariah court system that implements Syariah offences. It would be interesting to compare the constitutional foundation of the competency to administer Syariah offences in Malaysia and in Aceh since Malaysia adopt the system of federalism in contrast to Indonesia that adopt a unitary system of government. Plurality of the court system in Aceh will provide some insight into the same plurality that exist in Malaysia. The paper concludes with an observation about the future of the implementation of Syariah offences in Malaysia and in Aceh.